Importance of techniques and technology in cotton irrigation (Texas Journal of Engineering and Technology, 2024)
Today, due to climate change, the demand for water is increasing day by day everywhere in the world, the effective use of limited water resources, and the demand for irrigation water is increasing. In this regard, the available limited water resources are becoming scarce. Economical use of existing limited water resources and sources is considered one of the most urgent tasks of today. Analysis of data on the rational management of limited water resources in our province and their effective use, increasing the efficiency of water resources use in the field, the wide use of modern water-saving irrigation technologies and the possibilities of their application to production, analyzes on solving problems, Ending excessive water loss is the main task of today